2016
DOI: 10.1016/j.bbmt.2015.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin for the Prophylaxis of Acute Graft-versus-Host Disease in Patients Undergoing HLA-Matched Related Donor Allogeneic Hematopoietic Stem Cell Transplantation (allo-HCT)

Abstract: Statins possess potent immunomodulatory effects that may play a role in preventing acute GVHD (aGVHD) following allogeneic hematopoietic cell transplantation (allo-HCT). We performed a Phase II study of atorvastatin for aGVHD prophylaxis when given to allo-HCT recipients and their HLA-matched sibling donors. Atorvastatin (40mg/day) was administered to sibling donors, beginning 14 days before the anticipated start of stem cell collection. Allo-HCT recipients (n=40) received atorvastatin (40mg/day) in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
3
11
2
Order By: Relevance
“…In contrast to our initial report [22], the prospective trial by Efebera et al evaluating "2-pronged" atorvastatin use in matched sibling donor/recipient pairs reported a higher II to IV acute GVHD rate (30% at day +100) [34]. This difference seemed to result largely from the unusually high rates of isolated upper gastrointestinal (UGI) acute GVHD in the study by Efebera et al (where isolated UGI GVHD accounted for 42% of grade II to IV and 35% of grade I to IV acute GVHD at day +100).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our initial report [22], the prospective trial by Efebera et al evaluating "2-pronged" atorvastatin use in matched sibling donor/recipient pairs reported a higher II to IV acute GVHD rate (30% at day +100) [34]. This difference seemed to result largely from the unusually high rates of isolated upper gastrointestinal (UGI) acute GVHD in the study by Efebera et al (where isolated UGI GVHD accounted for 42% of grade II to IV and 35% of grade I to IV acute GVHD at day +100).…”
Section: Discussioncontrasting
confidence: 99%
“…15,16 Oral atorvastatin treatment of NZB/NZW mice reduced T-cell GVHD Retrospective analysis Statin intake of the recipient correlates with lower GVHD incidence 2008 [60] GVHD Retrospective analysis Donor statin treatment is connected to reduced GVHD incidence in patients 2010 [55] GVHD Retrospective analysis. Recipient statin treatment is connected to reduced GVHD incidence in patients 2010 [56] GVHD Prospective phase II trial of atorvastatin for aGVHD prophylaxis Donor and recipient treatment with atorvastatin is effective as prophylaxis for GVHD 2013 [57] GVHD Phase II study of atorvastatin for aGVHD prophylaxis Atorvastatin did not provide any benefit to standard GVHD prophylaxis alone 2016 [59] GVHD Phase II study to evaluate the safety and efficacy of atorvastatin-based aGVHD prophylaxis Preliminary efficacy of atorvastatin for aGVHD prevention was seen 2017 [58] Abbreviations: aGVHD, acute graft-versus-host disease; CEL, contrast-enhancing lesions; CRP, C-reactive protein; ESR, erythrocyte sedimentation rate; GVHD, graft-versus-host disease; LDL-C, low-density lipoprotein cholesterol; MS, multiple sclerosis; RA, rheumatoid arthritis; SLE, systemic lupus erythematosus. proliferation and cytokine production when the T cells were isolated from the treated mice and tested in vitro.…”
Section: Statins In Slementioning
confidence: 99%
“…addition of atorvastatin to standard aGVHD prophylaxis did not provide a benefit with respect to GVHD rates. 59…”
Section: Statins In Gvhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these data from the mouse model, subsequent clinical trials using statin prophylaxis in both patients/donors (Hamadani et al , ) or using treatment of donors only (Rotta et al , ) reported low GVHD rates. Conversely, one negative trial was reported where donors and patients received statins as prophylaxis leading to low rates of grade III‐IV aGVHD but unusually high rates of isolated upper intestinal tract acute GVHD (Efebera et al , ). A pharmacological approach targeting the proteasome with bortezomib was shown to reduce aGVHD in the mouse model by reducing pro‐inflammatory cytokines (Sun et al , ).…”
Section: Microbiome Metabolites and Immune Regulation In Agvhd Biologymentioning
confidence: 99%